2020
DOI: 10.21508/1027-4065-2020-65-5-58-65
|View full text |Cite
|
Sign up to set email alerts
|

A teenager with a severe form of COVID-19

Abstract: П андемия новой коронавирусной инфекции COVID-19-болезни, вызванной вирусом SARS-CoV-2,-стала глобальной медицинской и эко-номической катастрофой в масштабах, не наблюдавшихся за последние 100 лет [1]. Несмотря на множество проблем, существующих во взрослом © Коллектив авторов, 2020 Адрес для корреспонденции: Мазанкова Людмила Николаевна-д.м.н., проф., зав. кафедрой детских инфекционных болезней Российской медицинской академии непрерывного профессионального образования,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The authors of the two case reports suggested that patients might be at a high risk for secondary infection after receiving tocilizumab or tocilizumab combined with glucocorticoid. They suggested that clinicians should use tocilizumab with caution and screen for latent tuberculosis before medication (Mazankova et al, 2020;Moideen et al, 2020).…”
Section: Search Resultsmentioning
confidence: 99%
“…The authors of the two case reports suggested that patients might be at a high risk for secondary infection after receiving tocilizumab or tocilizumab combined with glucocorticoid. They suggested that clinicians should use tocilizumab with caution and screen for latent tuberculosis before medication (Mazankova et al, 2020;Moideen et al, 2020).…”
Section: Search Resultsmentioning
confidence: 99%